The Urgency of Maturity to Get Married and Its Relevance to Family Life Goals - Darussamin, Zikri; Armansyah, Armansyah; Zikri, Ahmad (AL-ISTINBATH : Jurnal Hukum Islam, 2023)
This paper aims to explore aspects of the legitimacy of limiting the age of marriage from the perspective of maqâshid al-syarî'ah. Early marriage is regarded as highly common ini Indonesia. According to data for 2020, 1 in 9 or almost 11% of Indonesian girls get married before becoming 18 years old. Through Law Number 16 of 2019 about Amendments to Law Number 1 of 1974 about Marriage, the government is trying to suppress the practice of early marriage  through limiting the age of marriage to 19 years. Research methods are qualitative-explanative method, this paper attempts to analyze the texts and doctrines of fiqh scholars relating to the age of marriage and relate them to the purpose of marriage through the point of view of maqâshid al-syarî'ah. Through this method, it has been discovered that that marriage is a noble Islamic law and the only institution that legalizes sexual relations as a primary need (daruri) for human being in order to realize the maintenance of religion (hifzh al-dîn) through the avoidance of the practice of adultery, as well as maintaining the sustainability of mankind (hifzh al-nasl). Considering that marriage is closely related to responsibilities, it can be concluded that arrangement 19 years as the ideal age for marriage is considered to be in line with the maqâshid of marriage. Carrying out underage marriages will cause mafsadah, because it has negatives effect on health, fertility and causes bad social impacts so that maqâshid marriage cannot be realized.